Dicationic ionic liquid‐grafted UiO‐66 as efficient catalyst for CO2 conversion into cyclocarbonate under cocatalyst‐free and solventless conditions - Li, Fangfang; Hou, Xiaofang; Zhou, Ying‐Hua (Applied organometallic chemistry, 2024)
CO2 chemical fixation offers a feasible approach for carbon mitigation and high‐value utilization, but it is still challenging to develop an efficient catalyst for CO2 conversion into cyclic carbonate. Herein, the triethylenediamine‐derived dicationic ionic liquids (DIL‐X, X = Cl, Br, and I) were grafted into UiO‐66 linkers through self‐assembly of Zr4+ ions and the mixed ligands of terephthalic acid and DIL‐bearing dicarboxylic acid, resulting in UiO‐66‐DIL‐Xn, (n designated as molar amount of the feeding DIL‐X). Their catalytic performance was evaluated by the epoxide cycloaddition reaction in the absence of solvent and cocatalyst. Among them, the UiO‐66‐DIL‐Cl0.4 catalyst exhibited outstanding performance, with a chloropropene carbonate yield of 92% and a high selectivity of 99% under 0.1 MPa CO2 at 110 °C for 16 h. Its high activity could be ascribed to the cooperativity among Lewis acidity of MOF nodes, the enhanced CO2 absorption, and the strong nucleophilicity offered by halogen ions of ionic liquid‐modified MOF. Moreover, UiO‐66‐DIL‐Cl0.4 presented excellent recyclability and substrate extension. A potential catalytic mechanism for the epoxide‐CO2 cycloaddition into cyclic carbonate has been proposed. This work will shed light on the rational design of functionalized MOFs‐based catalysts for CO₂ utilization. Grafting dicationic ionic liquids into UiO‐66 can significantly improve the catalytic activity of CO2 cycloaddition with an epoxide in the absence of a cocatalyst and solvent.